Разъемный реактор для получения стержней поликристаллического кремния - Гаврилов П. М. Петр Михайлович; Бараков Б. Н. Борис Николаевич; Прочанкин А. П. Александр Петрович; Муравицкий С. А. Степан Александрович
опубл. 27.02.10